2011
DOI: 10.1525/auk.2011.128.4.810
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Migratory Connectivity of Gray Catbirds (Dumetella carolinensis) using Geolocator and Mark–recapture Data

Abstract: Resumen.-Comprender la conectividad entre poblaciones reproductivas y no reproductivas de aves migratorias es fundamental para nuestro conocimento de fenómenos biológicos como la dinámica poblacional y la dispersión. Además, nuestra habilidad para cuantificar la conectividad migratoria tiene consecuencias inevitables para la conservación y el manejo de especies que utilizan distintas localidades geográficas. La tecnología está causando avances rápidos en nuestra habilidad para seguir aves a lo largo de su cicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 11 publications
0
31
0
Order By: Relevance
“…To date, a number of geolocator studies have reported no statistical difference in return rates between tagged and control birds [12,24,39,40], but see [39,41,42]. Negative effects to breeding have been found in some studies, including greater fledgling mortality the year after tagging [43], later egg laying and lower nest success [41], although this was not the case for all species [42].…”
Section: Discussionmentioning
confidence: 99%
“…To date, a number of geolocator studies have reported no statistical difference in return rates between tagged and control birds [12,24,39,40], but see [39,41,42]. Negative effects to breeding have been found in some studies, including greater fledgling mortality the year after tagging [43], later egg laying and lower nest success [41], although this was not the case for all species [42].…”
Section: Discussionmentioning
confidence: 99%
“…(d) Band recovery data for connectivity Band recovery data can be used to independently assess migratory connectivity, and to supplement geolocator tracking data [8]. Analysis of North American band recovery data (1921-2010) for purple martins banded at breeding sites (n ¼ 2884 recoveries) identified 12 birds that were recovered in South America after autumn migration and before spring migration (see the electronic supplementary material, figure S1).…”
Section: Methodsmentioning
confidence: 99%
“…The geographic linkages provided by migratory animals and the habitats that they use are referred to as migratory connectivity. Understanding migratory connectivity has implications for the viability of species and thus for species conservation (Ryder et al 2011). With a new suite of smaller devices ranging from geolocators to satellite tags, researchers can help advance the knowledge of animal movement, the habitats needed for survival and key needs for conservation.…”
Section: Introductionmentioning
confidence: 99%